The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1002/14651858.cd008983.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccines in immunosuppressed adults with cancer

Abstract: Background Immunosuppressed cancer patients are at increased risk of serious influenza-related complications. Guidelines, therefore, recommend influenza vaccination for these patients. However, data on vaccine effectiveness in this population is lacking, and the value of vaccination in this population remains unclear. Objectives To assess the effectiveness of influenza vaccine in immunosuppressed adults with malignancies. The primary review outcome is allcause mortality, preferably at the end of the influenza … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 59 publications
1
32
0
3
Order By: Relevance
“…Confirmed influenza and pneumonia rates were lower with vaccination, and a reduction in hospitalizations following vaccination was observed. 10 Another prospective cohort study showed Influenza vaccination was associated with lower mortality among adult cancer patients. In spite of these favorable outcomes with immunization, coverage rates for these vaccines in adults are markedly lower than the rates among children and far below adult immunization goals.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmed influenza and pneumonia rates were lower with vaccination, and a reduction in hospitalizations following vaccination was observed. 10 Another prospective cohort study showed Influenza vaccination was associated with lower mortality among adult cancer patients. In spite of these favorable outcomes with immunization, coverage rates for these vaccines in adults are markedly lower than the rates among children and far below adult immunization goals.…”
Section: Discussionmentioning
confidence: 99%
“…Although concerns have been raised regarding the efficacy of vaccination in patients with malignant disease, studies demonstrate that patients with cancer-including those treated with chemotherapy-remain able to respond to vaccination and that influenza immunisation in this group reduces mortality [3,4]. Side-effects of both influenza and pneumococcal vaccines are mild, and similar to those experienced by the general population [3,[5][6][7]. Consequently, the UK Department of Health (DH) and the US Center for Disease Control (CDC) recommend that in the absence of contraindications, patients planned for cytotoxic therapy should be vaccinated against both S.pneumoniae and influenza [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A promising method for reducing the risk of influenza infection is vaccination. Therefore, various guidelines, including those described by the Center for Disease Control and Prevention, recommend the influenza vaccination, especially in cancer patients (3). However, vaccination coverage is still low among cancer patients (4).…”
Section: Introductionmentioning
confidence: 99%